Analisis Pengaruh Review Vlogger Terhadap Keputusan Pembelian Konsumen Pada Produk Kecantikan - Rahmah Aliyah; Fikri Mahesa Purba; Dini Lestari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify reviews, such as credibility, content quality, or vlogger personal experience, which have an impact on purchasing decisions and evaluate the level of consumer confidence in the information conveyed by vloggers regarding beauty products. there is a positive influence of Variable X (Vlogger Review) on Variable Y (Purchase Decision). This research method uses quantitative methods, the data in this study were obtained through the distribution of questionnaires distributed to respondents. Data analysis was carried out using the simple regression method. Based on research conducted on students of the Islamic Economics Department of UINSU by giving a questionnaire regarding the effect of Vlogger Reviews on purchasing decisions, the authors draw the conclusion that vlogger reviews have an effect on consumer purchasing decisions of students of the UINSU Islamic Economics Department. This is evidenced by the results of the t test which shows the sig value, for the effect of variable X on Y of 0.000 <0.05 and the value of t count 14.947> t table 1.984. Which means Ha is accepted and Ho is rejected. Thus, it can be concluded that there is a significant influence between variable X (Review Vlogger) and variable Y (Purchase Decision).